Mutation of Agr Is Associated with the Adaptation of Staphylococcus aureus to the Host during Chronic Osteomyelitis - Suligoy, Carlos M.; Lattar, Santiago M.; Noto Llana, Mariángeles; González, Cintia D.; Alvarez, Lucía P.; Robinson, D. Ashley; Gómez, Marisa I.; Buzzola, Fernanda R.; Sordelli, Daniel O. (Frontiers in Cellular and Infection Microbiology, 2018)
Selection pressures exerted on Staphylococcus aureus by host factors may lead to the emergence of mutants better adapted to the evolving conditions at the infection site. This study was aimed at identifying the changes that occur in S. aureus exposed to the host defense mechanisms during chronic osteomyelitis and evaluating whether these changes affect the virulence of the organism. Genome assessment of two S. aureus isolates collected 13 months apart (HU-85a and HU-85c) from a host with chronic osteomyelitis was made by whole genome sequencing. Agr functionality was assessed by qRT-PCR. Isolates were tested in a rat model of osteomyelitis and the bacterial load (CFU/tibia) and the morphometric osteomyelitic index (OI) were determined. The ability of the isolates to trigger the release of proinflammatory cytokines was determined on macrophages in culture. Persistence of S. aureus within the host resulted in an agrC frameshift mutation that likely led to the observed phenotype. The capacity to cause bone tissue damage and trigger proinflammatory cytokines by macrophages of the agr-deficient, unencapsulated derivative (HU-85c) was decreased when compared with those of the isogenic CP8-capsulated parental strain (HU-85a). By comparison, no significant differences were found in the bacterial load or the OI from rats challenged with isogenic Reynolds strains [CP5, CP8, and non-typeable (NT)], indicating that lack of CP expression alone was not likely responsible for the reduced capacity to cause tissue damage in HU-85c compared with HU-85a. The production of biofilm was significantly increased in the isogenic derivative HU-85c. Lack of agr-dependent factors makes S. aureus less virulent during chronic osteomyelitis and alteration of the agr functionality seems to permit better adaptation of S. aureus to the chronically infected host.